A grammar of the Nisgha language - Tarpent, Marie-Lucie (1987)
The Nisgha language, a member of the Tsimshianic family, is spoken in the Nass Valley of British Columbia. This grammar, based on recent first-hand research, provides an overview of the structure of the language. The first part covers the phonology, the main features of the morphology, and most of the syntax, including regular and predicate-focused clauses and the focusing system. The second part is a detailed reference guide to word-classes, word-formation and morphophonemic rules. The theoretical viewpoint is conservative and eclectic, but generally oriented towards functional explanation. Features of this language which are of current theoretical interest include syntactic ergativity, focusing, noun-incorporation, and reduplication. Graduate